2000
DOI: 10.1038/sj.bjp.0703109
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Z13752A, a combined ACE/NEP inhibitor, on responses to coronary artery occlusion; a primary protective role for bradykinin

Abstract: 1 The e ects on the responses to coronary artery occlusion of a combined ACE/NEP inhibitor (Z13752A) were examined in anaesthetized dogs. 2 A 1 h infusion of Z13752A (128 mg kg 71 min 71 intravenously) decreased arterial blood pressure (by 11+3%; P50.05) and increased coronary blood¯ow (by 12+4%, P50.05). There were no other signi®cant haemodynamic changes. 3 Z13752A inhibited both NEP and ACE enzymes both in dog plasma and in tissue (lung ACE; kidney NEP). Pressor responses to angiotensin I in vivo were inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Inhibition of kinin breakdown has been shown to be an effective method for inducing protection of the ischemic myocardium [102][103][104][105][106][107][108]. Administration of the ACE inhibitors enalapril or lisinopril, to rat intact hearts subjected to left coronary artery ligation (30 min) and reperfusion, produced a significant reduction in infarct size [109].…”
Section: Kininsmentioning
confidence: 99%
“…Inhibition of kinin breakdown has been shown to be an effective method for inducing protection of the ischemic myocardium [102][103][104][105][106][107][108]. Administration of the ACE inhibitors enalapril or lisinopril, to rat intact hearts subjected to left coronary artery ligation (30 min) and reperfusion, produced a significant reduction in infarct size [109].…”
Section: Kininsmentioning
confidence: 99%
“…It is important to compare the affinities of BK and a B 2 -receptor antagonist for B 2 -receptors in the absence or presence of ACE and NEP inhibitors for evaluating the role of ACE and NEP on BK degradation, because we have shown that captopril increases the affinity of BK to B 2 -receptor binding sites in bovine coronary arterial endothelial cells (Miyamoto et al 2000). Recently, several dual inhibitors of ACE and NEP have been developed for the treatment of hypertension, myocardial ischemia and coronary artery occlusion (Fournié-Zaluski et al 1994;Chatelain et al 1998;Rastegar et al 2000). However, some reports showed that a NEP inhibitor (phosphoramidon) did not further potentiate the maximal effect of ACE inhibitor (captopril) on BK-induced arteriolar dilation (Gao et al 1994) and BK degradation (Ishida et al 1989).…”
Section: Introductionmentioning
confidence: 97%
“…9) are some more novel ACE/NEP inhibitors. The latter compound has also shown efficacy against ventricular fibrillation and tachycardia in a canine model of coronary artery occlusion which is attributed to the protective effects of increased bradykinin levels 26 . The concept of triple vasopeptidase inhibition has recently gained interest.…”
Section: Fig 8: Chemical Structure Of the New Dual-action Receptor Amentioning
confidence: 99%